EGFR-targeted bacteriophage lambda penetrates model stromal and colorectal carcinoma tissues, is taken up into carcinoma cells, and interferes with 3-dimensional tumor formation - Huh, Haein; Chen, Ding-Wen; Foldvari, Marianna; Slavcev, Roderick; Blay, Jonathan (Frontiers in Immunology, 2022)
Colorectal cancer and other adult solid cancers pose a significant challenge for successful treatment because the tumor microenvironment both hinders the action of conventional therapeutics and suppresses the immune activities of infiltrating leukocytes. The immune suppression is largely the effect of enhanced local mediators such as purine nucleosides and eicosanoids. Genetic approaches have the promise of interfering with these mechanisms of local immunosuppression to allow both intrinsic and therapeutic immunological anticancer processes. Bacterial phages offer a novel means of enabling access into tissues for therapeutic genetic manipulations. Here, we generated spheroids of fibroblastic and cancer cells to model the 3-dimensional stromal and parenchymal components of colorectal tumours. We then examined the access and effects of epidermal growth factor (EGF)-presenting bacteriophage λ (EGF-λ) to evaluate this as a possible strategy for the delivery of targeted genetic interventions in solid cancers. Using flourescence-tagged wildtype bacteriophage λ (AF488-WT-λ) and AF488-EGF-λ, we showed that phage entry into these tumour microenvironments was possible and that the EGF ligand enabled efficient and persistent uptake into the cancer cell mass. EGF-λ became localized in the intracellular portion of cancer cells and was subjected to subsequent cellular processing. The targeted λ phage had no independent effect upon mature tumour spheroids, but interfered with the early formation and growth of cancer tissues without the need for addition of a toxic payload, suggesting that it might have beneficial effects by itself in addition to the genetic intervention delivered to the tumour. The interference with spheroid formation was persistent over the duration of spheroid culture. We conclude that targeted phage technology is a feasible strategy to facilitate delivery into colorectal cancer tumour tissue (and by extension other solid carcinomas) and provides an appropriate delivery vehicle for a gene therapeutic that can reduce local immunosuppression and/or deliver an additional direct anticancer activity.